Uji Adaptasi Wortel di Tanah Lempung Liat Berpasir Dataran Rendah Palangka Raya (Adaptation Test of Carrot at Sandy Clay Loam in Low-Land Areas of Palangka Raya) - Muhammad Anang Firmansyah; Twenty Liana; Wiwik Rahayu (Indonesian Center for Horticulture Research and Development, 2016)
Tanaman wortel (Daucus carota L.) menghendaki suhu udara optimal 18oC–21oC, suhu udara tersebut di daerah tropis umumnya tercapai pada ketinggian > 500–1.000 m diatas permukaan laut (dpl.). Upaya pengembangan wortel di dataran rendah bersuhu > 28oC di Indonesia belum banyak dilakukan. Tujuan penelitian untuk melihat daya adaptasi varietas wortel di dataran rendah 40 m dpl di Kota Palangka Raya. Penelitian disusun menggunakan rancangan acak kelompok dan diulang tiga kali. Perlakuan terdiri dari lima varietas, yaitu wortel import (Royal Chantenay, Nantes Improved, Flaker Giant), serta wortel lokal (Cisarua dan Batu). Hasil penelitian menunjukkan daya kecambah varietas Cisarua tertinggi pada 8, 10, 12, dan 14 hari setelah tanam (HST) hingga 202 tnm/m2. Tinggi tanaman 91 HST pada Flaker Giant tertinggi, yaitu 56,7 cm tidak berbeda nyata kecuali dengan varietas Nantes Improved. Jumlah daun pada 91 HST pada Cisarua terbanyak mencapai 11,3 helai/tnm dan berbeda nyata dengan varietas lainnya. Berat brangkasan basah dan kering varietas Flaker Varietas Giant tertinggi 61,20 g/tnm dan 7,32 g/tnm. Rasio berat brangkasan dan umbi basah terendah dicapai varietas Cisarua 0,89 dan Batu 0,64, dan berbeda nyata dengan wortel varietas import. Panjang umbi wortel tidak berbeda antarvarietas, yaitu 9,40–21,90 cm/umbi. Diameter umbi total dan hati umbi varietas lokal dan import tidak berbeda nyata kecuali dengan varietas Nantes Improved, masing-masing 26,00–27,63 mm dan 15,93–17,87 mm. Bobot umbi terberat dicapai varietas Cisarua 41,87 g disusul varietas Flaker Giant 32,3 g, diikuti bobot daging tertinggi pada varietas Cisarua 18,53 g dan berbeda nyata dengan varietas Nantes Improved. Tingkat kemanisan daging dan hati umbi wortel varietas Cisarua tertinggi, yaitu 8,87oBrix dan 7,43oBrix. Wortel varietas Cisarua memiliki adaptasi terbaik berdasarkan daya kecambah, bobot umbi, rendahnya tingkat serangan penyakit busuk daun, dan tingkat kemanisan daging umbi.KeywordsDaucus carota L.; Dataran rendah; Palangka RayaAbstractThe carrot (Daucus carota L.) is a plant that requires optimum temperature in the range of 18°C to 21°C. In the tropics, this temperature could be generally found in the highlands with height of >500–1,000 meters above sea level. In Indonesia, carrots farming development in the lowlands with temperatures >28oC has not been conducted. The aims of this study is to know adaptability of some carrots varieties grown in the lowlands areas, at 40 m above sea level in Palangka Raya. The research design used randomized block design with three replication. There are treatments consisting of five varieties of imported carrots namely, Royal Chantenay, Nantes Improved, Flaker Giant, including two local varieties namely Cisarua and Batu. The results showed that highest germination is dominated by local varieties of Cisarua at 8, 10, 12, and 14 days after planting, it was up to 202 plants/m2. The highest plant at the age of 91 days after planting (DAP), the variety of Flaker Giant reaches 56.7cm, although it not significantly different with the other varieties except Nantes Improved. The number of leaves at the age of age 91 DAP showed that most of Cisarua variety has11.3 pieces of leaf/plant and it is significantly different from other varieties. For stover weight, both in wet, and dry condition, the variety of Flaker Giant reached respectively 61.20 g/plant and 7.32 g/plant. Stover weight ratio and the lowest wet tuber was dominated by Cisarua that is 0.89, not significantly different with Local Batu, 0.64 but it was significantly different from other imported varieties of carrots. The length of carrot tuber leng this not different among varieties, that is 9.40 to 21.90 cm/tuber. Diameter of tuber and tubers core diameter of local and imported varieties were not significantly different except with Nantes Improved, which the range of each variety is between 26.00–27.63 mm and 15.93–17.87 mm. The heaviest weight was found at Local Cisarua, that is 41.87 g, followed by Flaker Giant, 32.3 g. For tuber weight, this is followed by Cisarua with weight of 18.53 g, it is highest and significantly different from Nantes Improved. For carrots weetness level, it was not significantly different. However, Cisarua has the value of 8,87oBrix, including its tuber core 7.43oBrix. Cisarua has good adaptation in low land, base on germination, tuber yield, attack of late blight and sweetness of tuber.